Mono- and co- culture biofilms of candida auris or candida albicans with staphylococcus aureus regulate cell viability and pro-inflammatory cytokine expression differently in oral cancer cell lines - Wan Ahmad Kamil, Wan NurHazirah; Mokhtar, Munirah; Baharom, Madia Baizura; Bandara, H.M.H.N; S. Alrashdan, Mohammad; Cirillo, Nicola; Arzmi, Mohd Hafiz (John Wiley and Sons Inc., 2025)
Background: Candida species and Staphylococcus aureus are nosocomial pathogens associated with immunocompromised individuals, especially oral cancer patients. This study elucidates the effects of mono- and co- culture biofilms of Candida albi- cans, Candida auris and S. aureus on cell viability and pro- inflammatory cytokine expression in healthy epithelial cells (hTERT TIGKs) and oral cancer (ORL- 48) cell lines. Methods: Mono- and co- culture biofilms of C. albicans, C. auris and S. aureus, developed using static biofilm for 72 h, were collected and filter sterilized (biofilm filtrate). Test cell growth medium (TCGM) was prepared for hTERT TIGKs and ORL-48 by mixing 20% (v/v) biofilm filtrate with 80% serum- free media. The cells were seeded in 96- well plates, and TCGM was added as treatment. The unstimulated media (UM), made of 100% serum- free media, served as control. After 24 h, cell viability was assessed using CCK- 8. Interleukin (IL)- 6 and IL- 8 expression was analysed using enzyme- linked immunosorbent assay (ELISA). Results: S. aureus consistently decreased cell vitality in co- culture as compared to mono- culture, C. albicans and C. auris in both cell lines. Co- culture of C. auris and S. aureus in cancer cells demonstrated significantly higher IL- 6 and IL- 8 expression than C. albicans (p < 0.05). Furthermore, co- culturing C. auris or C. albicans with S. aureus increases pro- inflammatory IL- 8 expression in oral cancer cell lines compared to mono- cultures of respective Candida. Conclusion: Co- culturing C. auris or C. albicans with S. aureus reduced cell viability and increased pro- inflammatory IL- 8 expression in oral cancer cell lines, suggesting that interkingdom interaction may regulate oral carcinogenesis.